A Non-Invasive Approach to Predict Risk In Dengue Hemorrhagic Fever (DHF) Using Bioelectrical Impedance Analysis - Abdul Rahim, Herlina; Shair, Ezreen Farina; Taib, Mohd Nasir (2009)
The purpose of this study was to validate a single BIA for predicting the risk in DHF in dengue patients in the Hospital Universiti Kebangsaan Malaysia (HUKM). The BIA technique based on the passing of low-amplitude electrical current less than 1 mA (500 to 800!A) with frequency 50kHz. During hospitalization, 210 patients who are 119 males and 91 females serologically confirmed DF and DHF patients were tested using single BIA. By using multiple regression analysis, race, reactance, complication, headache and the day of fever were found independent determinants of predicting the risk. Hence, this novel approach of BIA technique can provide rapid, non-invasive, and promising method for classifying and evaluating the status of the DHF patients.